Cleisostoma luopingense, a new species of Orchidaceae from Yunnan, China - Wu, Xun-Feng; Wang, Yu-Qian; Chi, Kuan-Bo; Liu, Qiang; Wang, Wen-Hua (Phytotaxa, 2021)
Cleisostoma luopingense, a new species of Orchidaceae, is described and illustrated from Yunnan Province, China. It is morphologically similar to C. williamsonii, but can be easily distinguished from the latter in having unbranched inflorescence and laxly placed 6–10 flowers; elliptic petals (size: 3.0–3.2 × 1.8–2.0 mm); back wall callus of spur yellow, T-shaped and mid-lobule deeply bilobed at base, column without stelidia.